2015
DOI: 10.1377/hlthaff.2015.0127
|View full text |Cite
|
Sign up to set email alerts
|

Women Saw Large Decrease In Out-Of-Pocket Spending For Contraceptives After ACA Mandate Removed Cost Sharing

Abstract: The Affordable Care Act mandates that private health insurance plans cover prescription contraceptives with no consumer cost sharing. The positive financial impact of this new provision on consumers who purchase contraceptives could be substantial, but it has not yet been estimated. Using a large administrative claims data set from a national insurer, we estimated out-of-pocket spending before and after the mandate. We found that mean and median per prescription out-of-pocket expenses have decreased for almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 20 publications
2
42
0
Order By: Relevance
“…Consistent with a recent study from a single large insurance carrier, 8 our findings demonstrate that implementation of the ACA has had substantial impact on cost-sharing for LARC for women with employer-sponsored commercial insurance, in particular dramatically increasing the proportion of women with $0 cost-sharing for LARC insertions. In interrupted time series analyses adjusting for patient and plan characteristics, rates of LARC use in our population rose steadily from 2010–2013, consistent with findings from a national survey that has shown steady increases from 2009–2012.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with a recent study from a single large insurance carrier, 8 our findings demonstrate that implementation of the ACA has had substantial impact on cost-sharing for LARC for women with employer-sponsored commercial insurance, in particular dramatically increasing the proportion of women with $0 cost-sharing for LARC insertions. In interrupted time series analyses adjusting for patient and plan characteristics, rates of LARC use in our population rose steadily from 2010–2013, consistent with findings from a national survey that has shown steady increases from 2009–2012.…”
Section: Discussionsupporting
confidence: 89%
“…5, 6 Despite some variability across method types, 6 evidence suggests that the ACA’s mandate overall translated into substantial reductions in cost-sharing for women in 2013. 7, 8 …”
Section: Introductionmentioning
confidence: 99%
“…Women who choose pills, patch, or ring are also often required to refill prescriptions at frequent intervals and these methods plus injections require women to manage use (e.g., taking a pill, changing a patch or ring, returning to the provider for the next injection). In addition, out-of-pocket costs across such methods average $9/month (Becker & Polsky, 2015). …”
mentioning
confidence: 99%
“…The roles of insurance coverage, co-pays, method cost-sharing, and confidentiality concerns with parental and school-based plans for younger women have received significant attention in light of the Affordable Care Act (ACA) [32,33]. Studies on the ACA and reproductive health have found that young women lack awareness and understanding of the ACA, family planning provisions under it, and even details of their own insurance plans [32].…”
Section: Discussionmentioning
confidence: 99%